Health and Justice: The Influence of Rawls' Theory on Health Law and Policy - Ade Sathya Sanathana Ishwara (CV. Era Digital Nusantara, 2026)
This research will discuss the principle of equal freedom and the principle of difference in the health context. The principle of equal freedom will emphasize the importance of universal access to health services as a basic right of every individual, while the principle of difference will discuss the need for policies that better support vulnerable groups to reduce inequality in the health sector. By applying Rawls's theory to the legal system and health policy, it is hoped that social justice can be improved for the entire community in the field of health services. Also, health systems can be designed to minimize inequities and ensure that health resources are distributed ethically and fairly.